INDONESIA IN TOBACCO CONTROL EFFORTS TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS TARGET 3.A - Gatari Dwi Hapsari (Sociae Polites, 2019)
This paper entitled Indonesia’s effort in Tobacco Control to achieve 3.a targets of Sustainable Development Goals in 2017-2019, which is strengthen implementation of FCTC in all countries, as appropriate. This study is a fascinating case to research due to the growing prevalence of child smokers in Indonesia every year. The damage caused by this problem is multi-dimensional, which includes damage to the economy, economy, and social, even threatening the narration of the Indonesia Golden Era of 2045. This study supported by a sustainable development concept, non-military threat concepts, also public policy to divide the research title. Keywords: Indonesia, smoker prevalency, sustainable development goals, tobacco control.